The Role of Digital Managerial Intervention in Micro and Small Business Empowerment: An Empowerment Theory Perspective - Manus, Victorio Chipta Gregory; Winarno, Agung; Hermawan, Agus (Journal of Applied Business, Taxation and Economics Research, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting economic growth and employment in Indonesia, but still face various challenges, particularly in terms of managerial management and the use of digital technology. This study aims to analyze MSME development through digital managerial interventions based on Empowerment Theory, using a case study of VJ Homebake Bakery & Eatery located in Mojokerto City, East Java. This study uses a qualitative approach with a participatory case study method, in which the researcher is directly involved in the business assistance process. The interventions carried out included optimizing the digital visibility of the business, strengthening branding and product packaging strategies, and implementing a digital payment system to improve operational efficiency. The analytical framework refers to Psychological Empowerment Theory, which emphasizes the cognitive, affective, and behavioral dimensions in the process of strengthening the capacity of business actors. The results of the study show that managerial digital interventions can improve digital literacy, confidence, and active participation of business owners in business management. In addition, increased business visibility and transaction efficiency have a positive impact on operational performance and customer engagement. These findings confirm that empowerment-based digital managerial interventions are an effective strategy in supporting the sustainability and competitiveness of MSMEs at the local level.